PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS PENDIDIKAN MATEMATIKA REALISTIK DENGAN STRATEGI HIPNOSIS MATERI HIMPUNAN KELAS VII - Muhammad Ilyas Yusuf (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2011)
Based on the fore research the RME approaches were one of the teaching approaches that could  improve  the  students’  activeness,  besides  the  theoretic  approach  showed  that hypnosis  was  one  of  the  ways  to  maximize  the  students’  brain  works,  so  that  RME  by using Hypnosis was used by the researcher to solve this problem. This study is proposed to  create  some  Mathematics  teaching instruments  based  on  valid  RME,  practice  and effective.  The  teaching  instruments  developed  are  Syllabi,  Lesson  Plan,  and  students’ activities worksheets, teaching CD, Learning Test. The method used in this research is 4- D by Thiagarajan that has been modified into 3-D such as; (1) define, (2) design and (3) develop.  The  results  of  this  research  are;  (1)  the  valuators  said  that  the  Mathematics teaching  Instruments  based  on  RME  was  valid;  (2)  the  researchers  said  that  the  RME using Hypnosis strategy was good (in score average 58), the researchers’ responses to the instruments  were  positive  (in  score  average  82%);  and  (3)  the  students’  proportion  that achieved  the  standardized passing  grade  in  each  cycle  was  80%;  the  last  is  the  average score in their prestige and activeness in the first cycle was 38,7 and 58,5; in the second cycle 77,9 and 66,4; in the third cycle 79,7 and  68,1.  The summary of this research was that the  Mathematics  teaching instrument based  on RME on the  sets concept was valid, practice  and  effective.  The  researcher  suggests  to  the  SMP  teachers  to  apply  the mathematics  teaching based on RME using Hypnosis Strategy on the other mathematics concepts. Key words: Realistic Mathematic Education (RME), Hypnosis.